A checklist of medically important flies (Order: Diptera) in the central region of Thailand - TANAWAT CHAIPHONGPACHARA; SEDTHAPONG LAOJUN; NITIWOOT JONGVISUTTISAN; PATCHARAPRON TUBSAMUT; APICHAYA DASOM (Society for Indonesian Biodiversity, 2018)
Chaiphongpachara T, Laojun S, Jongvisuttisan N, Tubsamut P, Dasom A. 2018. A checklist of medically important flies (Order: Diptera) in the central region of Thailand. Biodiversitas 19: 2134-2139. This study surveyed species of medically important flies in the central region of Thailand including Samut Songkram (coastal area representative), Bangkok (urban area representative), Phranakhon Si Ayutthaya (Lower alluvial area representative), Nakhon Sawan (upper alluvial area representative) and Sukhothai (mountainous area representative). This was done through a division of the central region into 5 areas, according to the landscape, including the coastal area, urban area, upper alluvial area, lower alluvial area and mountainous area. Flies were collected using insect nets and fly traps during July 2018. A total was 3872 adult flies, belonging to 4 subfamilies and 6 genera within 9 species were captured. The highest numbers of flies were found in the mountainous area, followed by coastal areas, upper alluvial area, urban area and lower alluvial area, respectively. All the study areas were within the central region of Thailand. The Chrysomya megacephala was the predominant species, with a total of 2953 adult flies captured. This was followed by the Musca domestica (n = 563), Achoetandrus rufifacies (n = 177) and Sacrophaga spp. (n = 137), respectively. The four species of flies collected in this study were Lucilia cuprina (n = 28), A. villeneuvi (n = 2), C. nigripes (n = 2) and Hemipygiopsis ligurriens (n = 2). The results of this study showed the distribution of flies, which is important information for diarrhoea vector control.